2019
DOI: 10.3389/fgene.2019.00756
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiles of mRNAs and miRNAs Reveal Molecular Characteristics of Multiple Organ Physiologies and Development in Pigs

Abstract: The pig (Sus scrofa) is not only an important livestock animal but also widely used as a biomedical model. However, the understanding of the molecular characteristics of organs and of the developmental skeletal muscle of the pig is severely limited. Here, we performed a comprehensive transcriptome profiling of mRNAs and miRNAs across nine tissues and three skeletal muscle developmental stages in the Guizhou miniature pig. The reproductive organs (ovary and testis) had greater transcriptome complexity and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that miRNA-mediated regulation in skeletal muscle development, particularly in target gene expression and signaling pathway regulation, is particularly important during skeletal muscle development [ 22 ]. Our previous RNA-seq analysis of skeletal muscle across 27 developmental stages revealed differential expression of miR-24-3p in Tongcheng and Landrace pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that miRNA-mediated regulation in skeletal muscle development, particularly in target gene expression and signaling pathway regulation, is particularly important during skeletal muscle development [ 22 ]. Our previous RNA-seq analysis of skeletal muscle across 27 developmental stages revealed differential expression of miR-24-3p in Tongcheng and Landrace pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that skeletal muscle development is regulated by multi-modal, multi-level, and multi-dimensional molecular targets and complex genetic mechanisms [ 22 , 23 ]. As crucial regulatory factors, miRNAs play a significant role in various biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle-specific miR-206 is described to be involved in proliferation and differentiation (Lam et al, 2019). Chen et al (2019) reported miR-1, miR-206 and miR133 family are DE miRNAs in skeletal muscle tissue of Guizhou miniature pig. But in our study, miR-206 was not detected as a DE miRNA in M-EXO.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular miRNAs have been found in the peripheral blood of a number of animal species, including bovines [14], poultry [15], and pigs [16]. As a result of their high stability in the body fluids of livestock, there is significant interest in the use of circulating miRNA as biomarkers for both the detection and the monitoring of disease progression in animals [17,18]. Expression-profiling studies conducted in domestic livestock have determined that miRNAs have distinct spatial (e.g., cell and tissue) and temporal expression patterns [19].…”
Section: Role Of Mirnas In Livestock Diseases and Conditionsmentioning
confidence: 99%